(3GbJUGOjGJ Gdfbd GdHMQj (B/s - (3eMehO, CMeO YHO GdefUas ((3GdGScfOQjI(B: s (3ecJHI heWHYI GdGTYGY GdafjI(B, s, 2001)
(3GbJUGOjGJ Gdfbd(B-(3GdJcGdja(B-(3GdShb GdedGMj(B-(3YbO GdGYGQI chSjdI dJehjd MjGRI GdSaf(B-(3GdSjGSGJ GdHMQjI(B-(3LgGR GdeThQIs
(3edGMb (B233(3U(B.s
Keywords: (3GdGbJUGOs; (3GdHhGNQs; (3Gdfbds